The environmental regulatory dictionary (Wiley & Sons, 2005)
Navigate your way through 40 CFR with this time-saving resource. The fourth edition of this popular reference provides definitions for more than 5,000 terms of the Environmental Protection Agency's Code of Federal Regulations Title 40 (40 CFR) to help readers better understand and follow these complex compliance regulations. Presented in alphabetical order for easy access, each term is defined using the exact wording found in 40 CFR, and every definition for a given term is included to ensure thoroughness